Unrest in South Thailand: contours, causes, and consequences since 2001 - Croissant, Aurel (Contemporary Southeast Asia, 2005)
In the past three years, southern Thailand has seen a rise of ethnic-based violence in its southernmost provinces. The principle objective of this article is to examine contours, causes and consequences of this recent development. The main argument is that although several contentious religious, cultural, economic and political issues lie at the root of ethnic violence, the drift toward militancy in the past three years must be explained by other factors. Historical concerns, religious differences, and social and economic marginalization cause local grievances and a latent crisis in inter-ethnic relations in south Thailand. Nonetheless recent Islamization of Muslim minority identity, policy failures of the sitting government and low quality conflict management account more for the increased violence in recent years. These factors created changes in the "enabling environment" that are allowing insurgency in south Thailand to grow. While the overall assessment for conflict resolution in the short term is negative, the political fallout of the unrest may strike the already faltering democratic consolidation a heavy blow.(Contemp Southeast Asia/DÜI)